Humanização da produção: gestão, competências e desafios na relação líder-liderado para a obtenção da qualidade de vida no trabalho - Marasea, Daniela Carnio Costa; Castro, Gisele; Junqueira, Lílian (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper compared two small events companies, in which leadership and quality of life at work were analyzed through humanization in the leader-servant relationship. The purpose of this paper was to verify the influence of the leader on the work environment, including its consequences to the interpersonal relationship. An instrument with 73 assertions was applied containing a 6-point scale, evaluating the degree of concordance. Analysis performed by the simple descriptive statistics. The leaders posture and attitudes interfered negatively with the perception of the Quality of Life at Work in the company B. In the company A, the posture and the attitudes were positively evaluated. Keywords: Leadership; Quality of life at work; Interpersonal relationship; Management.